2022
DOI: 10.3389/fmicb.2022.884574
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial and vaginal microbiome in donkeys with and without clinical endometritis

Abstract: Endometrial and vaginal microbiomes are critical in the study of endometritis, which is an important cause of infertility in donkeys. Our objective was to investigate the difference of the endometrial and vaginal microbiomes between healthy donkey jennies (group C) and jennies with endometritis (group E). Endometrial and vaginal swab samples were collected, and the 16 s rRNA gene amplicon high-throughput sequencing technique was applied to identify the microbial composition in the samples. A similar microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…zooepidemicus isolates from individuals with reproductive disorders were found to carry a higher number of virulence factors genes than isolates from clinically healthy jennies [ 31 , 32 , 33 ]. Recent studies have revealed that the microbiome of the vagina of healthy jennies included mostly the phyla Proteobacteria (most abundant family: Moraxellaceae), Firmicutes (most abundant family: Lactobacillaceae), Bacteroidetes (most abundant family: Sphingobacteriaceae) and Actinobacteria (most abundant family: Corynebacteriaceae) [ 34 ].…”
Section: Bacteria In the Reproductive System Of Equidsmentioning
confidence: 99%
See 4 more Smart Citations
“…zooepidemicus isolates from individuals with reproductive disorders were found to carry a higher number of virulence factors genes than isolates from clinically healthy jennies [ 31 , 32 , 33 ]. Recent studies have revealed that the microbiome of the vagina of healthy jennies included mostly the phyla Proteobacteria (most abundant family: Moraxellaceae), Firmicutes (most abundant family: Lactobacillaceae), Bacteroidetes (most abundant family: Sphingobacteriaceae) and Actinobacteria (most abundant family: Corynebacteriaceae) [ 34 ].…”
Section: Bacteria In the Reproductive System Of Equidsmentioning
confidence: 99%
“…In sharp contrast to relevant results in mares, investigation of uterine infections of donkeys has been limited [ 33 , 34 , 63 ]. The uterine microbiome of healthy jennies was found to be composed mainly of the phyla Proteobacteria (most abundant family: Moraxellaceae), Firmicutes (most abundant family: Lactobacillaceae) and Actinobacteria (most abundant family: Corynebacteriaceae) [ 34 ].…”
Section: Bacteria In the Reproductive System Of Equidsmentioning
confidence: 99%
See 3 more Smart Citations